Italian design and Italianity in brand naming. Teaching activities in Italian as a second language - Gilardoni, Silvia (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
This paper examines the expression of Italian language and culture in brand naming for the Italian design sector, in order to identify linguistic and cultural elements to be integrated into teaching activities for the development of linguistic and intercultural competence in Italian as a second language. The research is based on the linguistic and semantic analysis of a corpus of brand names of Italian design companies and products, which has allowed us to consider the role of onomastic creativity in the spread of Italian language and culture in the world. The analysis is followed by some suggestions for planning teaching activities based on the use of Italian design brand names in the context of teaching and learning Italian as a second language.